Docking studies: In silico lipoxygenase inhibitory activity of some commercially available flavonoids - Arumugam Madeswaran; Muthuswamy Umamaheswari; Kuppuswamy Asokkumar; Thirumalaisamy Sivashanmugam; Varadharajan Subhadradevi; Puliyath Jagannath (Bangladesh Pharmacological Society, 2012)
This study deals with the evaluation of the cyclooxygenase inhibitory activity of flavonoids using in silico docking studies. In this perspective, flavonoids like morin, naringenin, taxifolin, esculatin, daidzein, genistein, scopoletin, galangin and silbinin were selected. Azelastine, a known lipoxygenase inhibitor was used as the standard. Docking results showed that all the selected flavonoids showed binding energy ranging between -3.93 kcal/mol to -3.36 kcal/mol when compared with that of the standard (-3.70 kcal/mol). Intermolecular energy (-5.72 kcal/mol to -4.56 kcal/mol) and inhibition constant (1.31 mM to 3.43 mM) of the ligands also coincide with the binding energy. Morin contributed better lipoxygenase inhibitory activity because of its structural parameters.